2021
DOI: 10.1016/j.ajem.2021.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Association between laboratory parameters and CT severity in patients infected with Covid-19: A retrospective, observational study

Abstract: Introduction: Patients diagnosed with COVID-19 have presented to emergency departments (EDs) worldwide with a wide range of symptoms. In this study we reported the clinical, laboratory and radiological features of the cases diagnosed with COVID-19. Methods: This is a single-center, retrospective, descriptive, and observational study. The patients who have admitted to ED between March 11 and May 31, 2020 and diagnosed COVID-19 infection. Results: 130 (73 male and 57 female) patients with COVID-19 polymerase cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 29 publications
3
21
1
3
Order By: Relevance
“…In contrast, the results of our study showed no association between smoking and COVID-19 severity. Our study reported that the incidence of SARS-CoV-2 infection was associated with underlying comorbidities, the most common of which was DM, followed by HTN, as described in most previous literature [4] , [19] , [28] , [29] , [30] , [36] , [37] . In line with our findings, Marhl et al [38] reported a higher risk of COVID-19 among patients with diabetes due to the association between the dysregulation of ACE2.…”
Section: Discussionmentioning
confidence: 56%
“…In contrast, the results of our study showed no association between smoking and COVID-19 severity. Our study reported that the incidence of SARS-CoV-2 infection was associated with underlying comorbidities, the most common of which was DM, followed by HTN, as described in most previous literature [4] , [19] , [28] , [29] , [30] , [36] , [37] . In line with our findings, Marhl et al [38] reported a higher risk of COVID-19 among patients with diabetes due to the association between the dysregulation of ACE2.…”
Section: Discussionmentioning
confidence: 56%
“…Although the definitive diagnosis of COVID-19 disease is the RT-PCR test, many routine and non-routine biological and biochemical parameters have been examined for their diagnostic values and clinical outcomes [ [2] , [3] , [4] , [5] , [6] , [7] ]. In the Cochrane database, 21 studies that include the laboratory data of 56,585 non-COVID-19 patients and 14,126 COVID-19 patients were reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…It was declared a pandemic by the World Health Organization (WHO), with almost 400-600 k new cases daily, and it is responsible for more than 2.5 million deaths [ 1 ]. COVID-19 disease causes clinical manifestations, ranging from asymptomatic cases to severe pneumonia, and even to sepsis, multiorgan failure, and acute respiratory distress syndrome (ARDS) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coronaviruses invade the lungs, as well as the blood system, digestive system, and circulatory system (52). Therefore, the disease severity assessed by chest CT may correlate with laboratory inflammatory and immune biomarkers (53). The severity of lymphopenia and infection correlated with the severity of COVID-19 (54).…”
Section: Discussionmentioning
confidence: 99%